Pendekatan Lean dan Six Sigma untuk Manajemen Mutu di Transportasi Laut : studi kasus - Heykhal, Muhammad (Politeknik Pelayaran Sumatera Barat, 2025)
This case study investigates the application of an integrated Lean and Six Sigma (Lean Six Sigma/LSS) approach to improve quality management in the maritime transport industry. This qualitative research uses the DMAIC (Define, Measure, Analyze, Improve, Control) framework as a methodological guide. Data were collected through in-depth interviews with key personnel and an analysis of internal documents from a shipping company. The results show that the application of LSS was able to significantly address major operational issues, particularly related to schedule delays and fuel cost inefficiency. In the Define phase, the problem was identified and measured quantitatively. The Measure phase used real-time data to establish a performance baseline and identify variation. The analysis in the Analyze phase revealed that the root causes of the issues were a combination of poor coordination, static route planning, and inefficient work procedures. The solutions designed in the Improve phase included dynamic route optimization and the standardization of loading and unloading processes. Finally, the Control phase ensured the sustainability of the improvements through a performance dashboard and routine audits. The study concludes that LSS is not merely a quality improvement methodology but a business strategy capable of enhancing competitive advantage. Its application requires adaptation by leveraging technology and a commitment from all organizational levels. These findings provide a practical framework for the maritime industry to achieve greater efficiency, reliability, and safety.